CellTrix Pro: bioengineered scaffold kit for successful MSC differentiation / Nur Sufiah Zulkifli ... [et al.] - Zulkifli, Nur Sufiah; Ab-Rahim, Sharaniza; Koh, Ching Theng; Muhamad, Mudiana (2024)
The CellTrix Pro kit is an innovative biomaterial scaffold designed to facilitate the differentiation of mesenchymal stem cells (MSCs). This kit aims to address key challenges in tissue engineering and regenerative medicine by providing a scaffold that closely mimics the natural extracellular matrix that meet the structural and biological parameters, thus creating an ideal environment for MSCs growth and differentiation. The CellTrix Pro kit features a three-dimensional scaffold made from biocompatible and biodegradable materials, included with optimized cocktails of growth factors and growth media. These components are tailored to support MSCs differentiation to osteogenic, chondrogenic, and adipogenic. The porosity microarchitecture of the scaffold enhances cell viability, proliferation, and differentiation efficiency. In vitro studies demonstrated the kit’s superior performance, showing a significant improvement in the speed and reliability of MSCs differentiation compared to conventional methods making it more efficient and reproducible for MSCs differentiation. The CellTrix Pro kit accelerates the production of high-quality, specialized cells suitable for various therapeutic applications with a straightforward and easy-to-follow protocol, ensuring that researchers can consistently achieve high- quality results. With broad applications in tissue repair, and disease modeling, CellTrix Pro kit offers a promising solution for treating degenerative diseases and injuries. It provides researchers with a powerful tool to advance stem cell biology and develop new therapeutic strategies. In conclusion, the CellTrix Pro kit represents a significant advancement in MSCs differentiation technology, with the potential to revolutionize regenerative medicine and improve patient outcomes.